Analysis Effect of Nano Chitosan Coating on The Quality of Shallot Bulbs (Allium ascalonicum L. var. Bauji) - Della Widya Puspita; Erma Prihastanti; Sri Widodo Agung Suedy; Agus Subagio (Jurnal Biodjati, 2022)
Shallots are bulb-shaped commodities that are difficult to maintain in new conditions because they are easily damaged. An effective effort to prevent deterioration of food quality during storage is by coating it using nano chitosan. The effectiveness of nano chitosan is influenced by particle size which related to the ratio of chitosan and STPP (sodium tripolyphosphate). This study aimed to determine the effect of nano chitosan coating with the addition of different ratios of chitosan and STPP and the appropriate ratio of chitosan and STPP on nano chitosan as a coating to maintain the quality of shallot bulbs (Allium ascalonicum L. var. Bauji). This study used a completely randomized design (CRD) method with four treatments and five replications. The treatments of this research were P0= Control, PI= Nano chitosan ratio of chitosan: STPP 1:3, P2= Nano chitosan ratio of chitosan:STPP 1:4, and P3= Nano chitosan ratio of chitosan:STPP 1:5. The variables of this study were the percentage of damage, the percentage of diameter shrinkage, weight loss, color, hardness, and moisture content. Data were analyzed using the ANOVA test and continued with the DMRT test. The application of nano chitosan coating on shallot bulbs could reduce damage, shrinkage of tuber diameter, weight loss, color, hardness, and decrease in water content better than the control treatment. The best results were shown by treatment P3 (1:5) with a percentage of damage of 8%, diameter shrinkage of 20.20%, weight loss of 18.40%, total color change of 54.45, hardness of 226.23 N, and a decrease in water content of 4.65% at the final water content of 79.09%.